Prevalence and epidemiological associates of novel psychedelic use in the United States adult population. (September 2019) - Sexton, James D; Crawford, Michael S; Sweat, Noah W; Varley, Allyson; Green, Emma E; Hendricks, Peter S
Background: Novel psychedelics approximate classic psychedelics, but unlike classic psychedelics, novel psychedelics have been used by humans for a shorter period of time, with fewer data available on these substances. Aims: The purpose of this study was to determine the prevalence of novel psychedelic use and the associations of novel psychedelic use with mental health outcomes. Methods: We estimated the prevalence of self-reported, write-in lifetime novel psychedelic use and evaluated the associations of novel psychedelic use with psychosocial characteristics, past month psychological distress, and past year suicidality among adult respondents pooled from years 2008–2016 of the National Survey on Drug Use and Health (weighted n =234, 914, 788). Results: A fraction (weighted n =273, 720; 0.12%) reported lifetime novel psychedelic use. This cohort tended to be younger, male, and White, have greater educational attainment but less income, be more likely to have never been married, engage in self-reported risky behavior, and report lifetime illicit use of other drugs, particularly classic psychedelics (96.9%). (2-(4-Bromo-2, 5-dimethoxyphenyl)ethanamine) (2C-B) (30.01%), (2, 5-dimethoxy-4-iodophenethylamine) (2C-I) (23.9%), and (1-(2, 5-dimethoxy-4-ethylphenyl)-2-aminoethane) (2C-E) (14.8%) accounted for the majority of lifetime novel psychedelic use. Although lifetime novel psychedelic use was not associated with psychological distress or suicidality compared to no lifetime novel psychedelic use or classic psychedelic use, relative to lifetime use of classic psychedelics but not novel psychedelics, lifetime novel psychedelic use was associated with a greater likelihood of past year suicidal thinking (adjusted Odds Ratio (aOR)=1.4 (1.1–1.9)) and past year suicidal planning (aOR=1.6 (1.1–2.4)). Conclusion: Novel psychedelics may differ from classic psychedelics in meaningful ways, though additional, directed research is needed.